Copper-Polymer Nanocomposites: An Excellent and Cost-Effective Biocide for Use on Antibacterial Surfaces - Paez-Collio, M; Paez-Collio, M; Azocar-Guzman, M; Azocar-Guzman, M; Tamayo-Villarroel, L; Tamayo-Villarroel, L (Elsevier Ltd, 2016)
The development of polymer nanocomposites with antimicrobial properties has been a key factor for controlling or inhibiting the growth of microorganisms and preventing foodborne diseases and nosocomial infections. Commercially available antibacterial products based on silver-polymer are the most widely used despite the fact that copper is considerably less expensive. The incorporation of copper nanoparticles as antibacterial agents in polymeric matrices to generate copper-polymer nanocomposites have presented excellent results in inhibiting the growth of a broad spectrum of microorganisms. The potential applications in food packaging, medical devices, textiles and pharmaceuticals and water treatment have generated an increasing number of investigations on preparing copper based nanocomposites and alternative polymeric matrices, as potential hosts of nano-modifiers. This review presents a comprehensive compilation of previous published work on the subject, mainly related to the antimicrobial activity of copper polymer nanocomposites. Within all the phenomenology associated to antibacterial effects we highlight the possible mechanisms of action. We discuss the differences in the susceptibility of Gram negative and positive bacteria to the antibacterial activity of nanocomposites, and influencing factors. As well, the main applications of copper polymer-metal nanocomposites are described, considering their physical and chemical characteristics. Finally, some commercially available copper-polymer nanocomposites are described. © 2016 Elsevier B.V.